2018
DOI: 10.1097/md.0000000000011686
|View full text |Cite
|
Sign up to set email alerts
|

Short interval of biopsy to robotic-assisted laparoscopic radical prostatectomy does not render any adverse effects on the perioperative outcomes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Beyond expectant management, patients with localized PCa have two primary options: radical prostatectomy (RP) or radiation therapy. RP may be conducted through laparoscopic or robot-assisted (RARP) techniques and may be performed within as little as 2 weeks from the time of biopsy [ 38 ]. A recent systematic review and meta-analysis of two randomized controlled trials and 9 prospective studies indicated no significant difference between the open, laparoscopic or RARP techniques in terms of complications, biochemical reoccurrence, urinary continence and erectile function, although RARP resulted in significantly lower blood loss [ 39 ].…”
Section: Prostate Cancer Backgroundmentioning
confidence: 99%
“…Beyond expectant management, patients with localized PCa have two primary options: radical prostatectomy (RP) or radiation therapy. RP may be conducted through laparoscopic or robot-assisted (RARP) techniques and may be performed within as little as 2 weeks from the time of biopsy [ 38 ]. A recent systematic review and meta-analysis of two randomized controlled trials and 9 prospective studies indicated no significant difference between the open, laparoscopic or RARP techniques in terms of complications, biochemical reoccurrence, urinary continence and erectile function, although RARP resulted in significantly lower blood loss [ 39 ].…”
Section: Prostate Cancer Backgroundmentioning
confidence: 99%